2007
DOI: 10.1016/j.msea.2006.12.090
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured titania/hydroxyapatite composite coatings deposited by high velocity oxy-fuel (HVOF) spraying

Abstract: Nanostructured titania/hydroxyapatite composite coatings deposited by high velocity oxy-fuel (HVOF) spraying Gaona, M.; Lima, R. S.; Marple, B. R.Contact us / Contactez nous: nparc.cisti@nrc-cnrc.gc.ca. AbstractPure nanostructured titania (TiO 2 ) and blends with 10 and 20 wt% hydroxyapatite (HA) powders were sprayed onto Ti-6Al-4V substrates using a high velocity oxy-fuel (HVOF) system. The feedstock powders employed in this work were engineered to exhibit similar particle size distributions in order to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 23 publications
0
38
0
2
Order By: Relevance
“…For example, HA was combined with Bioglass Ò (Novabone Products, Alachua, FL) [748,749] and with other glasses [750] to form glassceramics biocomposites. Other reinforcement materials for calcium orthophosphates are differentiated by either shape of the fillers, namely, particles [751,752], platelets [753,754], whiskers [484,755,756], fibers [757][758][759], or their chemical composition: zirconia and/or PSZ [250, 743-746, 755, 760-793], alumina [250,751,754,[793][794][795][796][797][798][799][800][801][802], titania [307,747,752,[803][804][805][806][807][808][809][810][811][812][813][814][815][816][817], other oxides [818-821], silica and/or glasses …”
Section: Biocomposites With Glasses Inorganic Materials and Metalsmentioning
confidence: 99%
“…For example, HA was combined with Bioglass Ò (Novabone Products, Alachua, FL) [748,749] and with other glasses [750] to form glassceramics biocomposites. Other reinforcement materials for calcium orthophosphates are differentiated by either shape of the fillers, namely, particles [751,752], platelets [753,754], whiskers [484,755,756], fibers [757][758][759], or their chemical composition: zirconia and/or PSZ [250, 743-746, 755, 760-793], alumina [250,751,754,[793][794][795][796][797][798][799][800][801][802], titania [307,747,752,[803][804][805][806][807][808][809][810][811][812][813][814][815][816][817], other oxides [818-821], silica and/or glasses …”
Section: Biocomposites With Glasses Inorganic Materials and Metalsmentioning
confidence: 99%
“…Therefore, the bioceramic coatings and calcium orthophosphates in particular, applied on Ti-based substrates, having a useful combination of biocompatibility, mechanical properties and relative stability in bodily environment, are subjects of an increasing interest for biomedical applications in modern orthopaedics and dentistry (Gaona et al, 2007;Salman et al, 2008;Soares et al, 2008;Thomas, 1994).…”
Section: Ti-based Implants With Bioceramic Coatingsmentioning
confidence: 99%
“…not initiating a response or interaction in contact with biological tissues. However, it was recently indicated that the titania surface bioactivity can be activated by different chemical treatments (Gaona et al, 2007;Zhao et al, 2007). This could provoke reconsideration of the titania coatings role, making them superior to other biomedical coatings, as so far TiO 2 is mostly recognized with its excellent corrosion resistance and high adhesion strength to different substrates (Liu et al, 2006).…”
Section: Ti-based Implants With Bioceramic Coatingsmentioning
confidence: 99%
“…Resalta por tanto el papel positivo que ha tenido la adición de óxido de titanio, con mejores propiedades mecánicas que la hidroxiapatita, en el aumento de la adherencia de los recubrimientos. Son pocos los grupos que hacen recubrimientos lo suficientemente similares como para ser comparados con éstos, pero el fenómeno citado es especialmente palpable en estudios como el de Lima, Marple y Gaona (12), que consiguen llegar a valores alrededor de 60-70MPa con HVOF, pero siempre con porcentajes elevados de titania (80-90%). Si se recurre a los estudios realizados por el propio grupo (13), se puede observar que las adherencias pre-inmersión son similares a las obtenidas, a pesar de aumentar el contenido relativo de hidroxiapatita en la mezcla.…”
Section: Caracterización Mecánicaunclassified
“…Por ello, se escoge el óxido de titanio como complemento de la hidroxiapatita, para provechar sus propiedades mecánicas y anticorrosivas. Estudios previos de recubrimientos con elevadas proporciones de TiO 2 constatan fuertes aumentos de propiedades como la adherencia (12). Asimismo, no se teme una reacción biológica adversa, ya que históricamente se sabe que el óxido de titanio es bioinerte o biocompatible.…”
Section: Introductionunclassified